(untitled) (Foundations in Clinical Pharmacy Practice, 2025)
Author Miss. Veera Naga Lalitha Nakkina, PharmD Scholar, Department of Pharmacy Practice, Koringa College of Pharmacy, Korangi, Kakinada, Andhra Pradesh, India Abstract Special population care addresses unique medication challenges in physiologically distinct patient groups requiring specialized knowledge, modified approaches, and heightened vigilance throughout the medication use process. Pediatric pharmacotherapy navigates developmental pharmacokinetics, weight-based dosing strategies, appropriate formulation selection, and age-specific monitoring parameters from neonates through adolescents with particular attention to medication safety and growth considerations. Geriatric medication management addresses pharmacokinetic alterations, pharmacodynamic sensitivity changes, polypharmacy challenges, and geriatric syndrome considerations through deprescribing methodologies, inappropriate medication avoidance, and simplified regimen development. Pregnancy and lactation pharmacotherapy balances maternal benefit against fetal or infant risk through teratogenicity assessment, placental transfer evaluation, lactation compatibility determination, and alternative therapeutic approaches when standard medications pose unacceptable risks. Renal impairment adaptations implement appropriate dosage adjustment methodologies, nephrotoxicity avoidance, dialysis considerations, and electrolyte management strategies based on kidney function assessment and medication clearance mechanisms. Hepatic dysfunction approaches address altered metabolism, protein binding changes, and encephalopathy risk through appropriate medication selection, dosage modification, and monitoring parameter adjustment based on liver disease severity classification. These specialized approaches ensure safe, effective medication use in populations with unique physiological considerations requiring modified pharmacotherapeutic strategies. Keywords: Developmental Pharmacokinetics, Altered Drug Disposition, Physiologic Adaptation, Vulnerable Populations, Organ Dysfunction VIEW PDF